The Role of Stakeholders in Protecting Victims of Hit-and-Run Crimes in North Sulawesi - Herlyanty Y. A. Bawole; Grace Yurico Bawole; Hironimus Taroreh (LifeSciFi, 2025)
The purpose of this study is to determine the role of stakeholders in providing protection for victims of hit-and-run crimes in traffic accidents. Law enforcement practices in Indonesia are often colored by things that are contrary to the principles that uphold human rights. Since ancient times, the human rights of Indonesian citizens have often been ignored or neglected, including victims of hit-and-run crimes in traffic accidents. Based on this history, the Indonesian government is trying to protect victims of crime, including victims of hit-and-run crimes in traffic accidents. Legal protection for victims of hit-and-run crimes in North Sulawesi has not yet fulfilled a sense of justice and every year the number of victims increases, both minor injuries, serious injuries, and even death. In this case, the role of institutions is very much needed. In conclusion, the role of stakeholders in protecting victims of hit-and-run crimes in North Sulawesi includes the role of the North Sulawesi Regional Police which uses penal and non-penal efforts. As well as the role played by the North Sulawesi Regional Government. This role is a concrete step in realizing the goal of protecting victims of hit and run accidents, especially those that occur in North Sulawesi.